Comparison of height and weight after 12 vs. 18 Gy cranial radiation therapy in pediatric acute lymphoblastic leukemia (ALL) patients - Albert C. Chen, MD, PhD; M. Fatih Okcu, MD, MPH; ZoAnn E. Dreyer, MD; Kala Y. Kamdar, MD; Rona Y. Sonabend, MD; Hilary S. Suzawa, MD; Eunji Jo, MS; Arnold C. Paulino, MD (Advances in Radiation Oncology, 2017)
Purpose: To compare the effect of 12 versus 18 Gy cranial radiation therapy (RT) on height and weight indices among pediatric patients with acute lymphoblastic leukemia (ALL). Methods and materials: Records of children with ALL who were 2 to 14 years old at the time of RT and were treated at a single institution between 2000 and 2011 were reviewed. Patients' height, weight, and body mass index were converted into z-scores using the Centers for Disease Control growth charts to normalize the values to number of standard deviations from the mean. These values were measured at the pre-RT clinic visit and subsequent yearly intervals. The z-scores of the growth indices were fitted into a generalizing estimating equations model and analyzed by various clinical factors. Results: A total of 48 patients met the study criteria, including 32 boys and 16 girls. The median age at the time of RT was 7 years (range, 2-14 years). Patients were separated into 2 dose groups: 12 Gy (n = 30) and 18 Gy (n = 18). Median follow-up was 4.9 years (range, 3.0-11.8 years) and 6.0 years (range, 3.1-10.5 years) and the median pre-RT height z-scores were −0.55 (range, −2.2 to 1.4) and −0.85 (range, −3.1 to 0.8) for the 2 groups, respectively (P = .65). Patients who received 18 Gy had a significant difference in change in height compared with those who received 12 Gy, who were able to maintain normal growth during the first 3 years of follow-up. This did not appear to be sex-specific, and there was no difference in change in weight or body mass index. Conclusions: Compared with 18 Gy, patients with ALL who received 12 Gy of cranial RT had less height impairment in the first 3 years post-RT, but further prospective studies are needed.